Cross‐Cultural Paediatric Neuropsychological Assessment: Key Considerations - Freddie O'Donald; Clara Calia; Sanne Franzen (Health Science Reports, 2025)
ABSTRACT Background and Aims Cross‐cultural paediatric neuropsychology faces important challenges in ensuring assessments are fair and valid across diverse cultural, linguistic, and socioeconomic backgrounds. This article aims to highlight key considerations and gaps in current practice, with a focus on supporting equitable neuropsychological assessment practices in increasingly diverse populations. Methods This perspective article draws on a structured narrative review of key literature and explores core themes in the cross‐cultural neuropsychological assessment of children, including test adaptation, developmental considerations, and interpreter‐mediated assessment. Results Three main areas are discussed: (1) the inconsistent adaptation of paediatric‐specific cognitive assessment tools across cultures, (2) the influence of cultural and educational factors on child development and test performance, and (3) the complexities of interpreter‐mediated neuropsychological assessment in paediatric settings. Although there are established tools and emerging guidance in adult neuropsychology, systematic, child‐focused cross‐cultural assessment frameworks remain underdeveloped. Conclusion Further research is needed to develop culturally responsive, developmentally appropriate, and standardised frameworks for paediatric neuropsychological assessment. This includes improving normative data sets, refining cross‐cultural adaptation processes, and developing interpreter protocols tailored to child assessments. These efforts are essential to ensure that assessments are equitable, accurate, and clinically useful across diverse populations.